The Learning of Social Multistatus Character Genre to Improve Politeness in Javanese Language - Utami, Sudi Esti; Kurniawati, Endang; Widayanti, Maria Johana Ari; Diner, Lispridona (International Journal of Language Education, 2019)
This research aimed to develop a learning model of social multistatus character genre in Speaking Class at Department of Study Javanese Language in Universitas Negeri Semarang. This model emphasized the performance of the use of the Java language orally. Students practiced in the form of monologue and dialogue by changing the social status of the character. Changing social status of the character offered to stimulate the application of the rules of the Java language in varied diversity. This study used the Research and Development approach. This study was conducted over 2 years. The first year activity was speaking learning model with the guided of various texts by changing the social status character. The products had been validated by several education of Java language experts. In the second year, seminars and application of these models had been conducted in the Speaking Class. The result showed the model was effective because students’ spoken ability increased. Students improved their learning spirit and they participated actively during the learning process.